Unusual Wrist Tremor: Unilateral Isometric Tremor?. (8th January 2014) - Zesiewicz, Theresa; Vu, Tuan; Carranza, Michael A.; Appelbaum, Rachel; Snyder, Madeline; Staffetti, Joseph S.; Allison, Kevin G.; Shimberg, William R.; Louis, Elan D.
Background: Tremors may be difficult to classify. Case Report: An 83-year-old male presented with an unusual left wrist tremor. The tremor could be reproducibly elicited by making a fist or carrying a weighted object (e.g., a shopping bag, bottle of water) of approximately 1 lb or more, and it intensified with heavier weights. The tremor was difficult to classify, although it shared features with isometric tremor. Discussion: This specific presentation of tremor has not been reported previously. We hope that the detailed description we provide will aid other neurologists who encounter this or similar tremors in their clinics.